Acute exacerbations of COPD and risk of lung cancer in COPD patients with and without a history of asthma. Issue 1 (1st January 2020) - Gagnat, Ane Aamli; Gjerdevik, Miriam; Lie, Stein Atle; Gulsvik, Amund; Bakke, Per; Nielsen, Rune
ABSTRACT: Rationale: There is limited knowledge on the effect of acute exacerbations in chronic obstructive pulmonary disease (AECOPD) on lung cancer risk in COPD patients with and without a history of asthma. This study aims to examine whether AECOPD is associated with risk of lung cancer, and whether the effect depends on a history of asthma. Methods: In the GenKOLS study of 2003–2005, 852 subjects with COPD performed spirometry, and filled out questionnaires on smoking habits, symptoms and disease history. These data were linked to lung cancer data from the Cancer Registry of Norway through 2013. AECOPD, measured at baseline was the main predictor. To quantify differences in lung cancer risk, we performed Cox-proportional hazards regression. We adjusted for sex, age, smoking variables, body mass index, and lung function. Measurements and results: During follow-up, 8.8% of the subjects with, and 5.9% of the subjects without exacerbations were diagnosed with lung cancer. Cox regression showed a significant increased risk of lung cancer with one or more exacerbations in COPD patients without a history of asthma, HRR = 2.77 (95% CI 1.39–5.52). We found a significant interaction between a history of asthma and AECOPD on lung cancer. Conclusions: AECOPD is associated with an increased risk of lung cancer in COPD patients without a history of asthma.